2013
DOI: 10.1152/ajpregu.00028.2013
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of vagal afferent nerve pathways regulating cough using Nav 1.7 shRNA silencing in guinea pig nodose ganglia

Abstract: Selective inhibition of vagal afferent nerve pathways regulating cough using Nav 1.7 shRNA silencing in guinea pig nodose ganglia. Am J Physiol Regul Integr Comp Physiol 304: R1017-R1023, 2013. First published April 10, 2013 doi:10.1152/ajpregu.00028.2013.-Adenoassociated virus delivery systems and short hairpin RNA (shRNA) were used to selectively silence the voltage-gated sodium channel NaV 1.7 in the nodose ganglia of guinea pigs. The cough reflex in these animals was subsequently assessed. NaV 1.7 shRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 26 publications
3
39
0
Order By: Relevance
“…The involvement of NKs also supports our previous assertions of jugular C-fiber involvement and against a role for either jugular Ad-fibers or nodose C-fibers (Ricco et al, 1996;Undem et al, 2004;Muroi et al, 2013).…”
Section: Treatmentsupporting
confidence: 88%
See 1 more Smart Citation
“…The involvement of NKs also supports our previous assertions of jugular C-fiber involvement and against a role for either jugular Ad-fibers or nodose C-fibers (Ricco et al, 1996;Undem et al, 2004;Muroi et al, 2013).…”
Section: Treatmentsupporting
confidence: 88%
“…Single, explosive coughing events evoked by mechanical stimulation of the airway mucosa in anesthetized guinea pigs-reflexes we attribute to activation of the bradykinin-insensitive nodose Ad fibers innervating the trachea, larynx, and main stem bronchi (Mazzone et al, 2009;Muroi et al, 2013)-were still present in all animals treated with a combination of the NK 1 , NK 2 , and NK 3 receptor antagonists (SR140333, SR48968, and SB223412, respectively; 3 mg·kg 21 each, i.p. ; n 5 3) or the vehicle for these antagonists (n 5 3).…”
Section: Bradykinin-evoked Coughingmentioning
confidence: 96%
“…Yet, indomethacin is also known to cause paradoxical cough as a side effect in a small subset (2.3%) of patients (www.ehealthme.com/ds/indomethacin/cough). In the guinea pig, Na v 1.7 knockdown by shRNA abolishes citric acid-induced cough (Muroi et al, 2013); this observation supports the feasibility of the third approach. This is in keeping with the antitussive action of nebulized lidocaine in patients with intractable cough (reviewed in Slaton et al, 2013).…”
Section: B Transient Receptor Potential Channels Insupporting
confidence: 63%
“…Another speculative benefit therefore of topically applied (inhaled) NaV-blocking drugs over muscarinic receptor antagonists is that even central deposition of a NaV blocker my lead to bronchodilation of more peripheral bronchi and bronchioles. Finally, we have recently reported that blocking NaV1.7 can inhibit action potential conduction along sensory C-fibers in the respiratory tract, leading to inhibition of undesirable sensations such as dyspnea and urge to cough, an effect that antimuscarinic drugs would not share (Muroi et al, 2011(Muroi et al, , 2013. It should be kept in mind that the present study focused on airways from healthy laboratory animals and donors that did not have asthma or COPD; both the expression and function of NaV channels may potentially be altered in the diseased state (Chahine and O'Leary, 2014).…”
Section: Discussionmentioning
confidence: 99%